Deduplication Analysis of Products In Digital Marketing - P. Amudhavalli; N. Rajalakshmi; K.S. Sindhu (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
As Digital Marketing is becoming more popular, the number of customer’s interpretation on brands is increasing promptly which makes it firmer for companies to evaluate their brand image and to digital market their products on the web. The Forensic Analysis is used to determine and analyze patterns of fraudulent activities on images. Pixel Analysis and Least square support vector machine are used to compare and associate the scores acquired from the images into one result per tweet. We selected these techniques to compare and find the accuracy of the Digital Marketing images with the received product’s images to identify the fraudulent activities on images in Digital Marketing. As the result of this project the customer can identify whether the received product is exactly what is given in the online purchase website.